Cancellation of Grant Deeds Made Before The Sub-District Head as the Official Officer of Temporary Land Deeds (Case Study of Decision No. 0200/Pdt.G/2019/PA.Pkj) - Fatkhul Bari, Ahmad (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
This research aims to analyze the judge's consideration of the cancellation of a grant deed made by the Subdistrict Head as the Temporary Land Deed Making Officer, and the resulting legal consequences based on Decision No.0200/Pdt.G/2019/PA.Pkj as well as examples of grant deeds made before the Subdistrict Head as the Temporary Land Deed Making Official. The method used in this research is a normative legal research method. The approach employed is qualitative. The data types and sources used are primary and secondary data. The data analysis method used in this research is prescriptive. From the results of this study are: Judge's Consideration Regarding the Cancellation of the Deed of Grant in the case of Decision No.0200/Pdt.G/2019/PA.Pkj the panel of judges who decided the cancellation of the grant based the reason for their decision that the cancellation of the grant based on the deed of grant number 222 j/BR/PK/XI/2007 dated November 23, 2007, was legally flawed, because it was not signed and/or fingerprinted/thumbprinted by the HUSBAND OF DEFENDANT 2 as the grantor. The legal consequences of the cancellation of the Deed of Grant by the Pangkajene Religious Court stated that the deed of grant was void and had no legal force and had fulfilled the provisions of Article 1688 of the Civil Code.